Social inequalities and health in rural Chiapas, Mexico: agricultural economy, nutrition, and child health in La Fraylesca Region - Héctor Ochoa-Díaz López; Héctor Javier Sánchez-Pérez; Magdiel Ruíz-Flores; Michael Fuller
The objective of this study was to investigate the association between farmers' socioeconomic conditions and their children's health in La Fraylesca, Chiapas. Data were collected using a cross-sectional survey of 1046 households (5546 individuals) sampled from locations in two counties situated in the study area. The survey included anthropometric measurements, a 24-hour dietary recall, stool tests, and childhood mortality data. Children of private farmers and "wealthy peasants" displayed better nutritional status, higher quality diet, lower prevalence of intestinal parasites, and a lower risk of dying than those whose parents were communal farmers, from ejidos, or "poor peasants". The results suggest that using volume of maize production as a classification method proved more valuable than land tenure to identify agricultural groups with different health status. It appears that the main determinants of health differentials are structural inequities in resource distribution. Thus, the impact of medical interventions on inequalities will be limited unless they are accompanied by redistribution of resources.